Limited decadal growth of mountain birch saplings has minor impact on surrounding tundra vegetation ... : Begränsad tillväxt av fjällbjörkplantor över årtionden har liten inverkan på den omgivande tundran ... - Scharn, Ruud; Negri, Isabel S.; Løkken, Jørn O.; Bacon, Christine D.; Antonelli, Alexandre; Hofgaard, Annika; Nilsson, R. Henrik; Björk, Robert (University of Gothenburg, 2022)
The study addresses two important issues in arctic treeline dynamics: • How do birch saplings, being the dominant treeline species, that have been established above treeline perform? • How do these birch saplings affect the surrounding tundra vegetation? For this, we collected species abundance measurements in 50 x 50 cm plots around birch saplings above the treeline near the Latnjajaure Field Station in northern Sweden. We compared these measurements with control measurements, and reference measurements taken below the treeline. We also looked at the growth (Diameter + Length) of birch saplings over 15 years (2001-2016). The data deposited includes the raw data, code, and statistical models used to analyze the data, and all output (figures and tables) used in the study. Further metadata can be found in the README file included with the data. GENERAL INFORMATION 1. Title of Dataset: Limited decadal growth of mountain birch saplings has minor impact on surrounding tundra vegetation 2. Author Information A. ... : Studien tar upp två viktiga frågor om fjällbjörkens, som är den dominerande arten i trädgränsen, förflyttning upp på kalfjället: • Hur klarar sig björkplantorna som har etablerats ovanför trädgränsen? • Hur påverkar dessa björkplantor den omgivande vegetationen på kalfjället? Vi samlade in data om artförekomsten av växter i 50 x 50 cm stora provytor runt björkplantor ovanför trädgränsen nära Latnjajaure Fältstation i norra Sverige. Dessa mätningar jämfördes med kontrollmätningar och referensmätningar gjorda under trädgränsen. Vi tittade också på björkplantornas tillväxt (diameter + längd) under de senaste 15 åren, från 2001 till 2016. De data som deponerats i datasetet omfattar rådata, kod och statistiska modeller som används för att analysera data samt alla utdata (figurer och tabeller) som används i studien. Ytterligare metadata finns i README-filen som ingår. ALLMÄN INFORMATION 1. Datasetets titel: Begränsad tillväxt av fjällbjörkplantor över årtionden har liten inverkan på den omgivande tundran 2. ...